2016
DOI: 10.1002/ajh.24384
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective study of rFVIIa, 4‐factor PCC, and a rFVIIa and 3‐factor PCC combination in improving bleeding outcomes in the warfarin and non‐warfarin patient

Abstract: In case of severe bleeding, the physician must rapidly and effectively halt bleeding without the risk of thromboembolic complications. Despite widespread use, no study has directly compared recombinant activated factor VII (rFVIIa), the rFVIIa and 3‐factor prothrombin complex concentrate (PCC) combination (“combination”), and 4‐factor PCC on their effectiveness in improving patient outcomes. This study examined the medical records of 299 patients, 65.2% on warfarin prior to admission, who received these hemost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 19 publications
(24 reference statements)
0
18
0
Order By: Relevance
“…Of these, full text was assessed, leading to the exclusion of another 109 studies, resulting in 17 studies that were included in the analysis. Studies included two prospective studies 23,24 and 15 retrospective studies, 25‐39 yielding a total of 3060 patients (Figure 1). Characteristics of the included studies are shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of these, full text was assessed, leading to the exclusion of another 109 studies, resulting in 17 studies that were included in the analysis. Studies included two prospective studies 23,24 and 15 retrospective studies, 25‐39 yielding a total of 3060 patients (Figure 1). Characteristics of the included studies are shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Characteristics of the included studies are shown in Table 1. Studies were conducted in patients undergoing cardiothoracic surgery (10 studies with a total of 1678 patients) 23‐25,28‐30,35‐37,39 in trauma patients (four studies with a total of 932 patients), 31‐33,38 in patients undergoing orthotopic liver transplantation (two studies with a total of 383 patients) 26,34 and in patients who were bleeding from various causes (one study with a total of 78 patients) 27 …”
Section: Resultsmentioning
confidence: 99%
“…52 In another retrospective review, a significantly greater proportion of patients achieved a target international normalized ratio of <1.3 when receiving a combination of 3 factor- prothrombin complex concentrate and recombinantFVIIa (79.4%) compared with patients who received either recombinant FVIIa (45.7%) or 4 factor- prothrombin complex concentrate (50.0%) alone; however, this combination therapy was associated with a significantly higher proportion of deep vein thromboses (18.7%) compared with either recombinant FVIIa (4.2%) or 4 factor- prothrombin complex concentrate (6.1%). 53 The high number of patients achieving international normalized ratio <1.3 and experiencing deep vein thromboses with the combination therapy might be indicative of “double dosing” of coagulation factors and the fact that 3 factor- prothrombin complex concentrates lack small amounts of anticoagulant factors (protein C and S) present in 4 factor- prothrombin complex concentrates. 53…”
Section: Resultsmentioning
confidence: 99%
“…53 The high number of patients achieving international normalized ratio <1.3 and experiencing deep vein thromboses with the combination therapy might be indicative of “double dosing” of coagulation factors and the fact that 3 factor- prothrombin complex concentrates lack small amounts of anticoagulant factors (protein C and S) present in 4 factor- prothrombin complex concentrates. 53…”
Section: Resultsmentioning
confidence: 99%
“…[63][64][65] Deloughery et al performed a retrospective analysis of patients on warfarin who received rFVIIa (n ¼ 35), rFVIIa in combination with 3F-PCC (n ¼ 102), or 4F-PCC (n ¼ 58), with the majority of patients presenting with intracranial bleeds. 66 All three groups achieved a mean postadministration INR 1.5. The combination group was able to achieve a mean INR 1.3 but was associated with a significantly higher incidence of deep vein thrombosis.…”
Section: Other Concentrated Coagulation Factor Productsmentioning
confidence: 88%